Analisis Efisiensi Waktu Bubble, Insertion, Merge, Dan Quick Sort Menggunakan Python - Sutanto, Daniel Septhiady; Chandra, Chandra Kirana; Wahyuningsih, Delpiah (LPPM Universitas Mulia, 2025)
Sorting is a fundamental process in data processing that plays an important role in increasing the efficiency of other algorithms. This study aims to conduct a comparative analysis of four classic sorting algorithms: Bubble Sort, Insertion Sort, Merge Sort, and Quick Sort. The comparison is based on three main paRAMeters: Execution time, algorithm Complexity. Testing was carried out experimentally using small to large random Datasets with test scenarios of 100, 150, 300 using the Python progRAMming language. The results showed that Merge Sort is the most efficient algorithm in terms of time because the average time required is 0.000165 seconds.